A structural model of factors influencing the practicum effectiveness of mathematics pre-service teachers in Vietnam - Le Thi Tuyet Hanh; Nguyen Thi My Hang (Institute of Advanced Engineering and Science, 2026)
Teacher education in Vietnam has undergone significant transformation following the implementation of the 2018 General Education Reform. Within this reform context, the teaching practicum plays a crucial role in enabling pre-service teachers to connect pedagogical knowledge acquired at universities with authentic classroom practice. This study developed and validated a structural model examining the factors influencing the practicum effectiveness (PE) of mathematics pre-service teachers in Vietnam. Using a quantitative research design, data were collected from 290 final-year pre-service teachers through a 25-item survey instrument representing six latent constructs: student characteristics (SC), training curriculum and practicum management (TCM), mentor teachers at partner schools (MT), university-based teacher educators (UTE), practicum conditions and innovations (PCI), and PE. The sample size satisfied the requirements for structural equation modeling (SEM) based on recommended minimum ratios of observations to estimated parameters. Confirmatory factor analysis (CFA) and SEM were conducted using SPSS 26 and AMOS 24 to examine the reliability and validity of the measurement model and the structural relationships among the constructs. The findings indicate that mentor teachers and SC exert significant direct effects on PE, whereas institutional and structural factors do not demonstrate significant direct effects in the structural model. These results highlight the critical role of relational and human factors in shaping practicum outcomes within authentic teaching contexts, particularly in the Vietnam’s ongoing educational reform.